RESPON PERTUMBUHAN TANAMAN KEDELAI HITAM TERINFEKSI MIKORIZA PADA TANAH MARJINAL - Purwaningsih, Ch. Endang (Widya Warta, 2013)
The aim of the study was to investigate the growth respons of black soybean of high yielding variety infected by mychorrhiza planted on marginal soils. Factorial Completely Randomized Block Design (CRBD) with three replicates was used in this experiment. The first factor was two levels of inoculation, namely M0: sterile soils without inoculation and M1: sterile soils inoculated with mychorrhiza 10 g polybag-1. The second factor was four levels of phosphate fertilizer (TSP) application, i.e. P0: without phosphate fertilizer, P1: 0,12 g, P2: 0,24 g, and P3: 0,36 g polybag-1, respectively. And the third factor was four levels of plant watering, i.e. A0: watered until field capacity, A1: watered 80% field capacity, A2: watered 60% field capacity, and A3: watered 40% field capacity. The plants were grown up on 5 kg of sterile soils added by legin, compost 30 g polybag-1, urea 0,48 g polybag-1, and KCl 0,36 g polybag-1, watered once in two days and harvested after eighty five days since planting time. The measurement parameters included percentage of mycorrhiza infection, plant height, number of leaves, and number of pods. The collected data were analyzed using Analysis of Variance (Anova), followed by Duncan’s Multiple Range Test (DMRT) at 5% level of significance. The result of this experiment showed that percentage of mychorrhiza infection was 80,38%. Symbiotic association with mychorrhiza increased plant height, number of leaves, and number of pods significantly.